ANALISIS IMPLEMENTASI KEBIJAKAN TIGA PROGRAM POKOK USAHA KESEHATAN SEKOLAH/ MADRASAH (TRIAS UKS/M) DI SMP KECAMATAN SRANDAKAN, KABUPATEN BANTUL - Mei Tika Isdarini; Antono Suryoputro; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2016)
Junior High Schools in Srandakan had already implemented Trias UKS/M policies. However, there are still found some problems and cases in reality dealing with the implementation process, seen from the aspect communication, resources, disposition, and bureaucratic structure. This research was located in Junior High Schools Srandakan, Bantul. The research type was qualitative using descriptive approach. The data collection was done by intensive interviews using interview guidelines and observation using checklist sheet for multiple variables. The informants in this research were the Headmaster, UKS teachers, and Chairman of the PMR at each school, Head of Community Welfare Section, Head of TU UPT PPD Srandakan as well as Head of Puskesmas Srandakan. The results showed that the policy of implementation Trias UKS/M was not optimal because the implementation has reached 10 out of 21 indicators. It was influenced by communication among the executive teams in the schools was not going well, especially in transmission. The resource variables had not fully support the implementation of Trias UKS/M policies yet, the human resources already well, but the financial aspect was not enough and there was no Decree and the facilities were inadequate. The attitude/disposition variables had not entirely support                                                                                                              the policies because the support of the relevant authorities was still weak. The bureaucratic structure variables had not totally support because there was no SOP. Suggestions in this research are to improve the communications among the executive teams and the mentor teams as well as involve Chairman of PMR in coordination meetings.